Transforming agriculture: Introductory remarks - Martha, Geraldo (2018)
Geraldo B. Martha Jr. SPECIAL EVENT Transforming Agriculture: Experiences and Insights from Brazil and Beyond Co-Organized by IFPRI and Embrapa MAY 15, 2018 - 12:15 PM TO 01:45 PM EDT